Police Violence: Reducing the Harms of Policing Through Public Health–Informed Alternative Response Programs - Spolum, Maren M.; Lopez, William D.; Watkins, Daphne C.; Fleming, Paul J. (American journal of public health (1971), 2023)
Police violence is a public health issue in need of public health solutions. Reducing police contact through public health–informed alternative response programs separate from law enforcement agencies is one strategy to reduce police perpetration of physical, emotional, and sexual violence. Such programs may improve health outcomes, especially for communities that are disproportionately harmed by the police, such as Black, Latino/a, Native American, and transgender communities; nonbinary residents; people who are drug users, sex workers, or houseless; and people who experience mental health challenges. The use of alternative response teams is increasing across the United States. This article provides a public health rationale and framework for developing and implementing alternative response programs informed by public health principles of care, equity, and prevention. We conclude with recommendations for public health researchers and practitioners to guide inquiries into policing as a public health problem and expand the use of public health–informed alternative response programs. (Am J Public Health. 2023;113(S1):S37–S42. https://doi.org/10.2105/AJPH.2022.307107 )